Commutator subgroups of the power subgroups of generalized Hecke groups - Koruoğlu, Ö.; Meral, T.; Sahin, R. (Algebra and Discrete Mathematics, 2019)
Let p, q ≥ 2 be relatively prime integers and let Hp,q be the generalized Hecke group associated to p and q. The generalized Hecke group Hp,q is generated by X(z) = −(z − λp)⁻¹ and Y (z) = −(z + λq)⁻¹ where λp = 2cos π/p and λq = 2 cos π/q.In this paper, for positive integer m, we study the commutator subgroups (Hᵐp,q)′ of the power subgroups Hᵐp,q of generalized Hecke groups Hp,q. We give an application related with the derived series for all triangle groups of the form (0; p, q, n), for distinct primes p, q and for positive integer n.